2006
DOI: 10.1063/1.2204847
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced microexplosion confined in a bulk of silica: Formation of nanovoids

Abstract: Articles you may be interested inInternal structure of the nanogratings generated inside bulk fused silica by ultrafast laser direct writing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 25 publications
(21 reference statements)
6
66
1
Order By: Relevance
“…32,67,68 Channels inside high purity silica and sapphire are required for electrophoresis applications where impurity ions are hampering high-resolution measurements of DNA fragmentation via electrical screening of an applied field and due to background emission intervening with photo-detection of photoluminescence. 69 It was demonstrated that faster etching occurs in densified silica by formation of Lewis base structure in which Si-O-Si angle is decreased. The decrease of the intensity ratio of a D 1 Raman line at 495 cm À1 to the D 2 at 606 cm À1 signifies decrease of 4-ring with respect to 3-ring structures.…”
Section: Photo-structuring By Optical Damage In Polymersmentioning
confidence: 99%
“…32,67,68 Channels inside high purity silica and sapphire are required for electrophoresis applications where impurity ions are hampering high-resolution measurements of DNA fragmentation via electrical screening of an applied field and due to background emission intervening with photo-detection of photoluminescence. 69 It was demonstrated that faster etching occurs in densified silica by formation of Lewis base structure in which Si-O-Si angle is decreased. The decrease of the intensity ratio of a D 1 Raman line at 495 cm À1 to the D 2 at 606 cm À1 signifies decrease of 4-ring with respect to 3-ring structures.…”
Section: Photo-structuring By Optical Damage In Polymersmentioning
confidence: 99%
“…However, the intensity at the focal point of the femtosecond laser beam where three beams interfere together could reach to 100 TW/cm 2 nearly. Such a high-energy influence within the focal volume ionized the silica glass quickly through the combined action of the avalanche and multiphoton processes [17,35]. A layer of plasma formed on the surface of the silica glass at the time of the laser pulse duration.…”
Section: The Formation Of the Triangular Lattice By Three Noncoplanarmentioning
confidence: 99%
“…Femtosecond laser pulse is also becoming into a powerful tool for microfabrication and micro-machining of various multi-functional structures in dielectric materials through multi-photon absorption because of its high-quality and damage-free processing. Up to now, many highquality material processing techniques have been achieved by using femtosecond laser pulses with the methods of directly writing [1][2][3][4][5][6][7][8][9][10] and holographic fabrication [11][12][13][14][15][16][17][18][19][20][21][22], such as waveguide [1], special diffractive optical elements (DOE) [4][5][6][7][8][9][10], micro-gratings [11][12][13][14][15], and photonic crystals [16][17][18][19][20]. Because multiphoton nonlinear effects play a major role in this process, the resulting change in refractive index or cavity formation can be highly localized only in the focal volume where the fluence is above a certain material dependent threshold, which makes it possible to micro-fabricate devices inside the bulk of transparent materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, the intensity at focus point would be approximate to 100 TW/cm 2 . So, high energy fluence within the focal volume would quickly ionize the silicate glass by the combined action of avalanche and multi-photon processes [13,33]. To reconstruct the optical vortex beam from the fabricated CGH, a collimated He-Ne laser beam was incident on the CGH inclined at 30° against the sample, and both the transmission and reflection pattern grating can be realized.…”
Section: Generating Optical Vortexmentioning
confidence: 99%